2014
DOI: 10.1890/es14-00046.1
|View full text |Cite
|
Sign up to set email alerts
|

Historical forest structure and fire in Sierran mixed‐conifer forests reconstructed from General Land Office survey data

Abstract: Abstract. Dry forests of the western United States (ponderosa pine, dry mixed conifer) are often considered at risk of uncharacteristic severe fires, but recent research has found historically extensive severe fire. This has left divergent perspectives about how to restore dry forests, protect people and infrastructure from fire, and interpret the ecological effects of large fires, such as the 2013 Rim fire, a human-set 104,000 ha fire in the western Sierra Nevada Mountains. To help resolve this uncertainty, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
150
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(164 citation statements)
references
References 68 publications
6
150
1
Order By: Relevance
“…Our estimate of past mixed conifer and ponderosa pine high severity fire (1-6%), which are similar to estimates from other work (Stephens et al 2007a, Mallek et al 2013, are much lower than those reported by Baker (2014) for the Sierra Nevada (31-39%). Perhaps information from contemporary restored fire regimes, for which fire severity patterns can be quantified more robustly, can provide insight.…”
Section: Relevance To Dry Forest Managementsupporting
confidence: 87%
See 3 more Smart Citations
“…Our estimate of past mixed conifer and ponderosa pine high severity fire (1-6%), which are similar to estimates from other work (Stephens et al 2007a, Mallek et al 2013, are much lower than those reported by Baker (2014) for the Sierra Nevada (31-39%). Perhaps information from contemporary restored fire regimes, for which fire severity patterns can be quantified more robustly, can provide insight.…”
Section: Relevance To Dry Forest Managementsupporting
confidence: 87%
“…Baker (2012Baker ( , 2014 used this system (GLO), which used eight trees per section (259 ha) that were marked to assist in the relocation of survey section corners, to reconstruct historical forest conditions in eastern Oregon and the Sierra Nevada. Four townships (or 144 sections) in eastern Oregon (Baker 2012) overlap an area that used similar historical transect data analyzed in this work (Hagmann et al 2013).…”
Section: Relevance To Dry Forest Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Ponderosa pine and dry mixed-conifer estimates, if pooled, would be roughly congruent with pooled estimates of 271 years in the Colorado Front Range [37] and 281-354 years in the western Sierra [38], but longer than the 217-year rotation on Black Mesa, northern Arizona [37], and the 175-year rotation on the Uncompahgre Plateau, which is just north of the San Juan Mountains [39].…”
Section: Moderate To High-severity Fires From Forest Atlases and Othementioning
confidence: 87%